Edukasi peningkatan kesadaran dan pemanfaatan aplikasi mobile JKN dalam pelayanan kesehatan - Sutaip Sutaip; Dewi Sulistyonigrum; Akbar Akbar; Tri Aulia Ramadhina; Ismi Nurul A’eni (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: The Social Security Agency on Health administers the national health insurance program, aiming to enroll all Indonesian citizens. Amidst rapid advancements in information technology, The Social Security Agency on Health has introduced digital innovations specifically the JKN mobile application to facilitate easier access to health insurance services for both current and prospective JKN-KIS members. Educating the public to effectively understand and utilize the JKN mobile application is crucial for ensuring they derive optimal benefits from health services. Purpose: To enhance public knowledge regarding the use of the JKN mobile application for BPJS Kesehatan health services. Method: The activity was conducted in May 2026 at the Jatibarang Community Health Center, involving 30 local residents from the center's service area as respondents. The initiative aimed to foster an understanding of how to utilize the JKN mobile application for The Social Security Agency on Health services. Evaluation was carried out using a